Proteolysis at a specific extracellular residue implicates integral membrane CLAG3 in malaria parasite nutrient channels. - Wang Nguitragool; Kempaiah Rayavara; Sanjay A Desai (PLoS ONE)
The plasmodial surface anion channel mediates uptake of nutrients and other solutes into erythrocytes infected with malaria parasites. The clag3 genes of P. falciparum determine this channel's activity in human malaria, but how the encoded proteins contribute to transport is unknown. Here, we used proteases to examine the channel's composition and function. While proteases with distinct specificities all cleaved within an extracellular domain of CLAG3, they produced differing degrees of transport inhibition. Chymotrypsin-induced inhibition depended on parasite genotype, with channels induced by the HB3 parasite affected to a greater extent than those of the Dd2 clone. Inheritance of functional proteolysis in the HB3×Dd2 genetic cross, DNA transfection, and gene silencing experiments all pointed to the clag3 genes, providing independent evidence for a role of these genes. Protease protection assays with a Dd2-specific inhibitor and site-directed mutagenesis revealed that a variant L1115F residue on a CLAG3 extracellular loop contributes to inhibitor binding and accounts for differences in functional proteolysis. These findings indicate that surface-exposed CLAG3 is the relevant pool of this protein for channel function. They also suggest structural models for how exposed CLAG3 domains contribute to pore formation and parasite nutrient uptake.